Pembinaan Anggota Jemaat tentang Perangi Adiksi Milenium Baru di Gereja Kristus Ketapang Pos Kelapa Gading - Amirrudin Zalukhu (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Program aims to provide spiritual and pastoral education to the congregation of Gereja Kristus Ketapang Pos Kelapa Gading in addressing the challenges of addiction in the modern era. Addiction is not merely related to technology or substance abuse, but reflects deeper issues of the heart, identity, and life direction. This activity employed a communicative and contextual lecture approach, with an emphasis on biblical values based on Ephesians 5:1–3 and Philippians 4:8–9. God's Word calls believers to live in love, purity, and self-control, directing their minds toward things that are noble and uplifting. The program also highlighted the importance of spiritual disciplines, involvement in healthy communities, and a lifestyle that reflects Christ's love. The church is expected to serve as a place of healing rather than judgment and to actively provide education and guidance that empowers the congregation. The outcome of this activity showed a positive response from participants, marked by personal reflection and renewed commitment to live out Christian values in everyday life.